The multiple worlds of ethnographic fieldwork: a personal account - Sax, William Sturman (Zeitschrift für Ethnologie, 2014)
In this autobiographical essay, I remember choosing to become an anthropologist because I wanted to explore "other worlds". I discuss what the notion of "other worlds" means to various disciplines, and why I came to the conclusion that the best way to explore such worlds was through ethnographic fieldwork. I address some of the criticisms of fieldwork, recount my experiences of "other worlds" while conducting fieldwork in India over several decades, and conclude with a few reflections about how all of this might relate to current discussions about the "ontological turn" in anthropology.
Gesehen am 19.10.2020
Keine DOI vorhanden